2017
DOI: 10.2106/jbjs.rvw.16.00065
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Osteochondral Lesions of the Talus

Abstract: ➢ Osteochondral lesions of the talus remain difficult pathological entities to treat and require the utilization of a combination of conventional radiographs, computed tomographic scans, and magnetic resonance images to determine osseous involvement. Along with the size of the lesion, these characteristics will dictate the treatment required to obtain a satisfactory clinical result.➢ Operative treatment should be reserved for patients who have mechanical symptoms following an acute osteochondral lesion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 86 publications
0
65
0
1
Order By: Relevance
“…Osteochondral lesions of the talus (OLTs) are common and may cause pain and dysfunction of the ankle. 5 , 7 , 8 , 27 OLTs can be a consequence of ankle sprain or trauma. Symptomatic OLTs that do not respond to nonoperative management, consisting of immobilization, protected weightbearing, nonsteroidal anti-inflammatory drugs, and/or physical therapy, need to be surgically treated.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Osteochondral lesions of the talus (OLTs) are common and may cause pain and dysfunction of the ankle. 5 , 7 , 8 , 27 OLTs can be a consequence of ankle sprain or trauma. Symptomatic OLTs that do not respond to nonoperative management, consisting of immobilization, protected weightbearing, nonsteroidal anti-inflammatory drugs, and/or physical therapy, need to be surgically treated.…”
mentioning
confidence: 99%
“… 6 , 18 However, in patients with full-thickness cartilage lesions and large subchondral cysts, the optimal treatment remains to be determined. 7 , 16 , 24 The large cavity of the debrided cyst may compromise the structural support of the articulation, and the subchondral bone defect may hinder cartilage regeneration. Recent studies 7 , 18 , 24 , 28 have shown that in patients with OLTs associated with large subchondral cysts, structural bone grafting, such as osteochondral autografts/allografts and autologous chondrocyte implantation, may provide good results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies have shown that scaffold-based therapies such as autologous matrix-induced chondrogenesis can be considered as an effective treatment strategy [5,6]. There are disputes between operation and non-operation [7], as well as among different surgical procedures [8][9][10]. Meanwhile, the same surgical procedure also has different effects among age groups.…”
Section: Introductionmentioning
confidence: 99%
“…8 De persistir el estímulo nocivo, se altera la capacidad de reparación tisular y la perfusión ósea, lo que genera el desarrollo de quistes subcondrales, dando inicio a una cascada eventos degenerativos hasta la artrosis. 9,10 El domo talar es la zona más afectada del retropie de ese tipo de lesiones. Elías y col., 11 establece que las lesiones en la región central del domo son las más frecuentes, seguidas de la región anterolateral y luego la posteromedial.…”
Section: Introductionunclassified